SUBURBAN ZONING OF BANDUNG RAYA AREA - Jupri, Jupri; Mulyadi, Asep (Indonesia University of Education, 2017)
Suburban area or urban periphery have an important role in supporting the development of the city. This role become increasingly important as the development of suburban areas from rural characteristics (agricultural) to urban characteristics (industry and services). The aim of this study is creating zone of suburban areas in four zones, that is: (1) Urban Frame Zone; (2) Rural Urban Frame Zone; (3) Urban Rural Frame Zone; (4) Rural Frame Zone. The method used in this research is spatial analysis based on proportion of agrarian land use with settlement land use. The data source used is the satellite imagery of Landsat 8 in 2015 in the suburbs area of Great Bandung. The result of this research is a Peripheral Zone Map of Bandung Raya in 1: 300.000. The map can be used as a reference in structuring and controlling development policies in Bandung Raya.